Cladosporium cladosporioides and C. tenuissimum Cause Blossom Blight in Strawberry in Korea - Nam, Myeong Hyeon (Mycobiology, 2015)
Blossom blight in strawberry was first observed in a green house in Nonsan, Damyang, and Geochang areas of Korea, between early January to April of 2012. Disease symptoms started as a grey fungus formed on the stigma, which led to the blossom blight and eventually to black rot and necrosis of the entire flower. We isolated the fungi purely from the infected pistils and maintained them on potato dextrose agar (PDA) slants. To test Koch's postulates, we inoculated the fungi and found that all of the isolates caused disease symptoms in the flower of strawberry cultivars (Seolhyang, Maehyang, and Kumhyang). The isolates on PDA had a velvet-like appearance, and their color ranged between olivaceous-brown and smoky-grey to olive and almost black. The intercalary conidia of the isolates were elliptical to limoniform, with sizes ranging from 5.0~10.5 × 2.5~3.0 µm to 4.0~7.5 × 2.0~3.0 µm, respectively. The secondary ramoconidia of these isolates were 0- or 1-septate, with sizes ranging betweem 10.0~15.0 × 2.5~3.7 µm and 8.7~11.2 × 2.5~3.2 µm, respectively. A combined sequence analysis of the internal transcribed spacer regions, partial actin (ACT), and translation elongation factor 1-alpha (TEF) genes revealed that the strawberry isolates belonged to two groups of authentic strains, Cladosporium cladosporioides and C. tenuissimum. Based on these results, we identified the pathogens causing blossom blight in strawberries in Korea as being C. cladosporioides and C. tenuissimum.